PENGARUH KREDIT MODAL KERJA TERHADAP PENINGKATAN PENDAPATAN PADA PT. BPR NUSUMMA JAWA TENGAH CABANG BLORA - Tri Suwarno (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2012)
Working capital loans are one source of revenue for a bank. The principle of prudence in the management of bank credit is needed because the credit risk and should be accountable for public funds to credit financing source of funds. This study to find out how strong and how big the influence of working capital contribution to earnings PT. Rural Bank Nusumma Central Java Branch Blora. Quantitative data derived from data used for working capital credit and income data from 2004 to 2008. Data processing techniques using correlation coefficient analysis and simple linear regression. The results showed that working capital is related to corporate earnings, the greater the working capital loans is thrown then the higher corporate earnings.